Neutrophil extracellular traps in the animal model of adenine-induced chronic kidney disease - Alexandra Gaál Kovalčíková; Gabriela Forraiová; Nelia Korotushak; Veronika Borbélyová; Diana Vavrincová-Yaghi; Peter Vavrinec; Ľudmila Podracká; Peter Celec (PLoS ONE, 2026)
Neutrophil extracellular traps (NETs) are suggested to play a role in chronic kidney disease (CKD). Whether they are indeed involved in the pathogenesis of animal models of CKD has not been proved. This study tested the hypothesis that a genetic deficiency of peptidylarginine deiminase 4 (PAD4) – a regulator of NETs production will protect mice from developing adenine-induced nephropathy as a model of CKD. Adult male Padi4 −/− mice and their wild-type counterparts received 100 mg/kg adenine or saline i.p. daily for 14 days. Markers of renal function and NETs-related biomarkers were assessed during the CKD induction in plasma and urine. In wild-type mice, adenine injections decreased body weight by 20% and increased plasma creatinine (twofold), neutrophil gelatinase-associated lipocalin (21-fold), and neutrophil elastase (4-fold). No significant differences were found between the Padi4 −/− and wild-type mice except the earlier increase in plasma creatinine in Padi4 −/− mice (day 3 vs. day 7). Analyses of neutrophil elastase and myeloperoxidase in plasma and urine suggest that neutrophils are activated in adenine-induced nephropathy, but the production of NETs seems not to be directly involved in the pathogenesis of this CKD model. Further studies should clear the role of NETs in other kidney disease models with clinical relevance.